An alternative approach toward 2-aryl-2H-pyrazolo[4,3-c]-quinolin-3-ones by a multistep synthesis - Lopez Rivilli, Marisa Juana (2010)
A series of 2-aryl-2H-pyrazolo[4,3-c]quinolin-3-ones derivatives 6 and 7 was conveniently prepared. A multistep synthesis was carried out starting from dichloro- and bromoanilines (1a-b) and diethyl 2-(ethoxymethylene)malonate using a slightly modified Gould-Jacobs reaction. In this work we present a novel chlorination strategy to prepare quinoline derivatives 4 in excellent yields as key intermediates in the synthesis of the target compounds. Several reaction conditions were evaluated to optimize the formation of pyrazoloquinolinone nucleus. Differences in chemical behavior of both chloroquinolinones 4a-b with aryl and benzyl-hydrazines are also discussed.